2015
DOI: 10.3846/16484142.2015.1048525
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Manufacturing Methods on the Tribological Properties of Rapeseed Oil Lubricants

Abstract: Tribological properties of rapeseed oils manufactured and processed by different methods and modified by the anti-wear additives were analysed. Tribological tests presented that unrefined rapeseed oil has better wear resistance compared to refined oil. Modification of rapeseed oil with 2% of special biological anti-wear additives has the greatest influence on refined rapeseed oil. Chemical analysis shows that refinement removes acids from oil. Refinement and lower acidity allows more efficient operation of spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…In the forestry and agricultural sectors are used environmentally friendly bio-based lubricants. It is way to save fossil resources and decrease negative impact of forestry and agricultural machinery to environment [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In the forestry and agricultural sectors are used environmentally friendly bio-based lubricants. It is way to save fossil resources and decrease negative impact of forestry and agricultural machinery to environment [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…As the chemical composition of olive oils may vary, it supposes the variety of interactions with materials even in the case of the same type of oils. For example, tribological tests of wear resistance properties of differently produced rapeseed oils show that unrefined rapeseed oil has better wear resistance as compared to that of refined oil [20]. In this study we explored the influence of different chemical composition and physical properties of olive oils produced from various districts in Morocco on their tribological performance and corrosion protection.…”
Section: Introductionmentioning
confidence: 99%
“…The second direction of development is to use green lubricants (for example, green oil, ionic liquid bio-lubricant, and biopolymers) made of natural materials; in addition to reducing the use of petroleum oil, this method enables the materials to be reused and recycled. Examples of such oils include natural vegetable oil [ 12 , 13 ], rice bran oil [ 14 ], rapeseed oil [ 15 ], and coconut oil [ 16 ]. Natural oils display favorable scalability; research has shown that with the addition of appropriate green additive(s), natural lubricating oils can exhibit lubrication properties identical to those of petrochemical lubricants [ 13 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%